CONTRIBUTION TO THE GEOCHEMICAL STUDY OF KANZI AND MVUANGU PHOSPHATE ROCKS IN THE LEMBA OIL SUB-BASIN OF CENTRAL CONGO - Deko Oyema Bruno; Emmanuel Kazinguvu Atibu; Dan Mandjumba Yenor; Dominique Wetshondo Osomba; Loma Wonga Mathias; John Pote Wembonyama (Romanian Journal of Petroleum & Gas Technology)
Located on the Congolese (DRC) side of the Lemba depression, our study area is the part that was returned by "ex-Zaïrep", just east of the concession currently operated by Perenco rep. Open to oil and mining exploration, we brought back phosphate rock samples from the field, which were analyzed by the Commissariat Général à l'Energie Atomique (CGEA) using the ED- XRF Xepos III spectrometer. These analyses were used to characterize the geochemistry of the Kanzi and Mvuangu phosphates. The results of the Chemical Analyses (Oxides) and Chemical Elements are as follows: (1) Major oxides (%:) Al2O3 (21,21 – 17,24); SiO2 (14,85 – 30,40); P2O5 (19,48 -13,34 %) finally Fe2O3 (8,544 – 10,74 %), and other oxides with concentrations in mg/kg (MnO, ZnO, Rb2O, SrO, ZrO2, Nb2O5, Sb2O5, Ta2O5); (2) Major Chemical Elements (%): Aluminum (11.22- 9.124); Silicon (6.939-14.21); Phosphate (8.5-5.823 %) and several trace metallic elements that will be exposed in another soil and sediment matrix to assess the state of the environment prior to mining and petroleum activities. The origin of these metallic elements, including heavy metals, rare earths and radionuclides, is phosphate. Phosphate rocks, such as apatite, may contain heavy metals, rare earths and radionuclides in their mineral structure. The gravity anomaly map of the Lemba sub-basin, where the phosphate sites are located, clearly shows that the phosphates of Kanzi in the south and Mvuangu in the north are not located in the central deposits, but in the upper parts of the sub-basin. These areas are potentially anticlines, which are geological structures capable of containing hydrocarbons. This study is a contribution to our knowledge of the phosphate resource in Kanzi and Mvuangu, and contribute to understanding the geological structures capable of containing hydrocarbons. It is also an important contribution in the field of geochemistry and gravimetry.